2016
DOI: 10.1186/s12884-015-0755-1
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes for women after obstetric fistula repair in Lilongwe, Malawi: a qualitative study

Abstract: BackgroundObstetric fistula affects a woman’s life physically, psychosocially, and economically. Although surgery can repair the physical damage of fistula, the devastating consequences that affect a woman’s quality of life may persist when she reintegrates into her community. This qualitative study assessed long-term outcomes among women who underwent obstetric fistula repair in Malawi. We explored three domains: overall quality of life before and after repair, fertility and pregnancy outcomes after repair, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 21 publications
2
61
1
Order By: Relevance
“…One study found no difference in the quality of life of women with persistent fistula before and after repair but did find a difference between those with successful and unsuccessful fistula closure, regardless of urinary incontinence symptoms . Qualitative studies further characterise the ongoing distress and social limitations in women with residual incontinence . Lower quality of life scores after fistula repair are found in unmarried women with no living children .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…One study found no difference in the quality of life of women with persistent fistula before and after repair but did find a difference between those with successful and unsuccessful fistula closure, regardless of urinary incontinence symptoms . Qualitative studies further characterise the ongoing distress and social limitations in women with residual incontinence . Lower quality of life scores after fistula repair are found in unmarried women with no living children .…”
Section: Discussionmentioning
confidence: 99%
“…25 Qualitative studies further characterise the ongoing distress and social limitations in women with residual incontinence. 6 Lower quality of life scores after fistula repair are found in unmarried women with no living children. 27 Time since repair has been described as a key factor in the recovery process.…”
Section: Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vaginal fistula is a debilitating condition that has pervasive consequences on women's psychological, social, physical and economic wellbeing. Without surgical intervention women with fistula face lifetime embarrassment, isolation, social stigmatization and marital separation [3][4][5]. Furthermore, they are prone to develop chronic vaginal and urinary tract infections, renal failure, pelvic inflammatory disease and amenorrhea [1,6].…”
Section: Introductionmentioning
confidence: 99%